Digestive symptoms in older adults: Prevalence and associations with institutionalization and mortality - AlAmeel, Turki (Pulsus Group Inc, 2012)
BACKGROUND: Digestive symptoms are common in adults. However, little is known about their prevalence in older adults and the association of digestive symptoms with institutionalization and mortality in community-dwelling older adults. OBJECTIVE: To determine the prevalence of digestive symptoms among older adults in Canada and whether they are associated with increased risk of institutionalization and mortality, independent of the effect of potential confounders. METHODS: The present study was a secondary analysis of data collected from community-dwelling participants 65 years of age and older in the Canadian Study of Health and Aging. Measures incuded age, sex, presence of digestive symptoms, cognition, impairment in activities of daily living (ADL) and self-reported health. Outcome measures included death or institutionalization over the 10 years of follow-up. RESULTS: Digestive symptoms were found in 2288 (25.6%) of the 8949 subjects. Those with digestive symptoms were older, with a mean difference in age of six months (P=0.007). Digestive symptoms were more common among women (28.4%) than men (20.3%), among individuals with poor self-reported health and those with an increased number of impairments in their ADLs (P<0.001). The presence of digestive symptoms was associated with higher mortality (HR 1.15 [95% CI 1.05 to 1.25] adjusted for age, sex, cognitive function and ADL impairment); however, this association was not statistically significant after adjusting for self-reported health. CONCLUSION: Although digestive symptoms were associated with increased mortality independent of age and sex, cognition and function, this association was largely explained by poor self-assessed health. Digestive symptoms were not associated with institutionalization